P137: Distal radial fractures: adequacy of reductions performed in the emergency department. (May 2020) - Atkinson, P.; Montazeri, R.; Wagg, J.; Mayich, J.; King, H.; Swan, J.; Fraser, J.; Benjamin, S.; Sibley, A.
Abstract : Introduction: Distal radial fractures (DRF) remain the most commonly encountered fracture in the Emergency Department (ED). The initial management of displaced DRFs by Emergency Physicians (EP) poses considerable resource allocation. We wished to determine the adequacy of reduction, both initially and at follow up. This data updates previously presented high level findings. Methods: We performed a mixed-methods study including patients who underwent procedural sedation and manipulation by an EP for a DRF. Radiological images performed at initial assessment, post-reduction, and clinic follow up were reviewed by a panel of orthopedic surgeons and radiologists blinded to outcomes, and assessed for evidence of displacement. Demographic data were pooled from patient records and included in statistical analysis. Results: Seventy patients were included and had follow-up completed. Initial reduction was deemed to be adequate in 37 patients (53%; 95% CI 41.32 to 64.10%). At clinic follow-up assessment, 26 reductions remained adequate; a slippage rate of 30% (95% CI of 17.37 to 45.90). Overall 7 patients (10%; 95% CI 4.65 to 19.51%) required revision of the initial reduction in the operating room. Agreement on adequacy of reduction on post-reduction radiographs between radiologists and orthopedic surgeons was 38.6% (95% CI -38.3 to -7.4, Kappa -0.229). The statistical strength of this agreement is worse than what would be expected by chance alone. There was no association found between age, sex, or of time of initial presentation and final outcomes. Conclusion: Although blinded review by specialists determined only half of initial EP DRF reductions to be radiographically adequate, only 10 percent actually required further intervention. Agreement between specialists on adequacy was poor. The majority of DRFs reduced by EPs do not require further surgical intervention.